2022
DOI: 10.1126/sciadv.abq0008
|View full text |Cite
|
Sign up to set email alerts
|

AFF3, a susceptibility factor for autoimmune diseases, is a molecular facilitator of immunoglobulin class switch recombination

Abstract: Immunoglobulin class switch recombination (CSR) plays critical roles in controlling infections and inflammatory tissue injuries. Here, we show that AFF3 , a candidate gene for both rheumatoid arthritis and type 1 diabetes, is a molecular facilitator of CSR with an isotype preference. Aff3 -deficient mice exhibit low serum levels of immunoglobulins, predominantly immunoglobulin G2c (IgG2c) followed by IgG1 and IgG3 but not IgM. Furthermore, Aff3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…1E, 1F), suggesting it functions differently in CSR. We conclude that Dot1l, Mllt10, and Mllt1 as well as the scaffold subunits of the SEC (Aff1), and SEC-L3 (Aff3) 31 , are proximal to AID in the nucleus and are participate in CSR.…”
Section: Multiprotein Complexes Dot1l and Sec Are Proximal To Aid And...mentioning
confidence: 89%
See 1 more Smart Citation
“…1E, 1F), suggesting it functions differently in CSR. We conclude that Dot1l, Mllt10, and Mllt1 as well as the scaffold subunits of the SEC (Aff1), and SEC-L3 (Aff3) 31 , are proximal to AID in the nucleus and are participate in CSR.…”
Section: Multiprotein Complexes Dot1l and Sec Are Proximal To Aid And...mentioning
confidence: 89%
“…ChIPs were performed as per standard protocol 31 . Briefly, for ChIPs from stimulated CH12-F3, 4x10 5 cells were stimulated in 10mL of media with CIT and cross-linked with 1% formaldehyde for 8 minutes at room temperature, at 16h post-stimulation.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Homeobox D9 (HOXD9) regulated and controlled many cells growth, and its overexpression can significantly enhance the migration, invasion and metastasis of hepatocellular carcinoma cells [ 44 ]. ALF Transcription Elongation Factor 3 (AFF3) was a susceptibility gene of autoimmune diseases [ 45 ]. Compared with normal samples, this gene was low expressed in gastric cancer, but its high expression was associated with poor prognosis of gastric cancer patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The largest GWAS study of the risk loci for subjects with T1DM was launched by GENIE, in which they found two single nucleotide polymorphisms (SNPs) were associated with ESRD: one in AFF3 gene ( P = 1.2 × 10 −8 ) and the other between the genes RGMA and MCTP2 ( P = 2.0 × 10 −9 ) ( 32 ). The mRNA expression of AFF3 is known to be relatively restricted to lymphocytes and brain tissues, encoding the AFF3 protein that facilitates the class switch recombination in B lymphocytes ( 33 ). AFF3 was also recognized as a candidate gene for rheumatoid arthritis, suggesting its modulatory effects on the immune system and inflammation that may contribute to the development of DKD ( 34 ).…”
Section: Genomicsmentioning
confidence: 99%